2020
DOI: 10.3390/ijms21020596
|View full text |Cite
|
Sign up to set email alerts
|

SLMP53-1 Inhibits Tumor Cell Growth through Regulation of Glucose Metabolism and Angiogenesis in a P53-Dependent Manner

Abstract: The Warburg effect is an emerging hallmark of cancer, which has the tumor suppressor p53 as its major regulator. Herein, we unveiled that p53 activation by (S)-tryptophanol-derived oxazoloisoindolinone (SLMP53-1) mediated the reprograming of glucose metabolism in cancer cells and xenograft human tumor tissue, interfering with angiogenesis and migration. Particularly, we showed that SLMP53-1 regulated glycolysis by downregulating glucose transporter 1 (GLUT1), hexokinase-2 (HK2), and phosphofructokinase-2 isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…It is often observed GLUT1 abnormal expression in tumour cells promote the ‘Warburg effect’ 29 . GLUT1 provide promising targets for tumour targeting therapy 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often observed GLUT1 abnormal expression in tumour cells promote the ‘Warburg effect’ 29 . GLUT1 provide promising targets for tumour targeting therapy 30 .…”
Section: Discussionmentioning
confidence: 99%
“…promote the 'Warburg effect'. 29 GLUT1 provide promising targets for tumour targeting therapy. 30 In this paper, our results show that the expression of GLUT1 was significantly promoted by MUC16.…”
Section: It Is Often Observed Glut1 Abnormal Expression In Tumour Cellsmentioning
confidence: 99%
“…Lactate is not only a waste for tumors; cancer cells also become more aggressive and resistant to therapy by acidifying their microenvironment. Low pH and lactate enable cancer cells to migrate, invade, promote angiogenesis, immune escape, and radioresistance [ 20 , 21 , 22 ]. The MCT family includes 14 members, among which MCT1-4 are catalyzing the proton-linked transport of pyruvate, lactate, and ketone bodies across the cell membrane [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a considerable number of studies have suggested that STYK1/NOK can activate various proliferation-related signaling pathways or molecules (31)(32)(33). A number of the signaling pathways have been reported to strictly regulate the expression and subcellular distribution of GLUTs, for instance, PI3K/Akt/mTOR, hypoxia-inducible factor-1, c-myc and tumor suppressor protein p53 (19,(34)(35)(36), which provides clues for the further exploration of the upstream molecular mechanism of GLUT3 in STYK1/NOK-overexpressing cells. This is the field of research that will be the focus of our work and studies in the future.…”
Section: Discussionmentioning
confidence: 99%